1989
DOI: 10.1007/bf00378661
|View full text |Cite
|
Sign up to set email alerts
|

The cellular slime mold guild and its bacterial prey: growth rate variation at the inter- and intraspecific levels

Abstract: A guild of cellular slime molds (CSM) consisting of two isolates from each of five species, representing two genera, and obtained from the same square meter of forest soil exhibited extensive growth rate variation when tested on a suite of 18 bacteria isolated from the same soil. Significant growth rate differences were found at each taxonomic level examined: among species of different genera, between genera, among species within genera, and between isolates (=clones) within species. The type of bacteria used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Given their global distribution, it is not surprising that dictyostelids can feed on a wide range of bacteria (Raper 1937; Raper and Smith 1939). Food “preferences” and competitive advantages amongst dictyostelid isolates have been observed (Eisenberg et al 1989; Horn 1971; Ketcham et al 1988; Ketcham and Eisenberg 1989). Experiments profiling gene expression during D. discoideum feeding on Gram positive or Gram negative bacteria suggest prey and predators communicate with each other using chemical cues (Carilla-Latorre et al 2008; Nasser et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Given their global distribution, it is not surprising that dictyostelids can feed on a wide range of bacteria (Raper 1937; Raper and Smith 1939). Food “preferences” and competitive advantages amongst dictyostelid isolates have been observed (Eisenberg et al 1989; Horn 1971; Ketcham et al 1988; Ketcham and Eisenberg 1989). Experiments profiling gene expression during D. discoideum feeding on Gram positive or Gram negative bacteria suggest prey and predators communicate with each other using chemical cues (Carilla-Latorre et al 2008; Nasser et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These cells phagocytose bacteria for food, but they are also infected and killed by some bacteria and colonized by others [2,4]. Early work showed that dictyostelids are limited in the soil by bacterial availability, and they show intra-and interspecific variation for growth on co-occurring bacteria [5][6][7]. Other work identified distinct sets of genes that regulate growth on Gram-negative versus Gram-positive bacteria, as well as physiological changes that take place upon phagocytosis of these two types of bacteria [8,9].…”
Section: Introductionmentioning
confidence: 99%